CONCEPT OF CONSTRUCTION OF CONTROL AND TEST STATION - Yurii Pribyliev B. Pribyliev (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The article proposes the concept of the construction of automated control and test station, which is based on the combination of the method of constructing the functional organization of the control and test station and the method of synthesizing the structure of the control and test station on the basis of software-hardware blocks, which allows simplifying and increasing the efficiency of the development of the control program, reducing the construction time and the volume of hardware control and test station, unification and further modification. The proposed concept allows to design the control and testing station with minimal costs. The developed concept of the construction of automated control and test station is presented in the form of a consistent solution of a number of tasks that combine in two stages. At the first stage, the synthesis of the informational appearance of the control and test station (determination of the plurality of functions implemented by the control and test station) is carried out, and the second - the synthesis of the structure of the control and test station on the basis of software and hardware blocks. Functional organisation of the control and testing station is the basis for the separation of the structural organisation of the control and testing station.